Interpersonal Communication of the Election Commission as a Strategy in Efforts to Improve the Political Efficiency of the Fisherman Community in Manggar District, Belitung Timur Regency - Asrikah Asrikah; Erman Anom (Ilomata International Journal of Social Science, 2023)
The KPU's communication target in general elections is to increase voter participation by giving them their voting rights in elections. Preliminary studies show that around 69.8% of 40 fishermen in Manggar District, East Belitung Regency, are still apathetic towards political processes such as elections and feel that their involvement in politics will have no impact. Therefore, the KPU then implemented an interpersonal communication strategy in an effort to increase the political efficacy of the fishing community in Manggar District. This study uses a qualitative descriptive method with data collection techniques of interviews, observation, and documentation. Data analysis used the Miles and Huberman interactive model, which consisted of the stages of data collection, data condensation, data presentation, and drawing conclusions. The results of the study found that the East Belitung KPU, together with members of the Manggar District Election Committee (PPK), held face-to-face meetings and discussions with fishermen groups as part of the KPU's outreach activities to the public. KPU has been open and honest in conveying any information related to the election, understanding the problems felt by fishermen, and providing support in the form of providing election education and knowledge to fishermen. In addition, KPU has also tried to build an atmosphere and interaction with fishermen to foster equality, as well as a communication approach that considers fishermen important. External factors such as the social environment or friends in the community and the candidate's vision and mission that can prosper the fishermen are factors that also influence the fishermen's perceptions and evaluations of elections and the political system in Indonesia.